Nucleotides Regulate Secretion of the Inflammatory Chemokine CCL2 from Human Macrophages and Monocytes. (7th September 2014) - Higgins, K. R.; Kovacevic, W.; Stokes, L.
Abstract : CCL2 is an important inflammatory chemokine involved in monocyte recruitment to inflamed tissues. The extracellular nucleotide signalling molecules UTP and ATP acting via the P2Y2 receptor are known to induce CCL2 secretion in macrophages. We confirmed this in the human THP-1 monocytic cell line showing that UTP is as efficient as LPS at inducing CCL2 at early time points (2–6 hours). Expression and calcium mobilisation experiments confirmed the presence of functional P2Y2 receptors on THP-1 cells. UTP stimulation of human peripheral CD14+ monocytes showed low responses to LPS (4-hour stimulation) but a significant increase above background following 6 hours of treatment. The response to UTP in human monocytes was variable and required stimulation >6 hours. With such variability in response we looked for single nucleotide polymorphisms in P2RY2 that could affect the functional response. Sequencing of P2RY2 from THP-1 cells revealed the presence of a single nucleotide polymorphism altering amino acid 312 from arginine to serine (rs3741156). This polymorphism is relatively common at a frequency of 0.276 (n = 404 subjects). Finally, we investigated CCL2 secretion in response to LPS or UTP in human macrophages expressing 312Arg-P2Y2 or 312Ser-P2Y2 where only the latter exhibited significant UTP-induced CCL2 secretion (n = 5 donors per group).